Perceptual-cognitive skill training and its transfer to expert performance in the field: Future research directions - Broadbent, D. P.; Causer, J.; Williams, A. M.; Ford, P. R. (European Journal of Sport Science, 2015)
Perceptual-cognitive skills training provides a potentially valuable method for training athletes on key skills, such as anticipation and decision-making. It can be used when athletes are unable to physically train or are unable to experience repeated key situations from their sport. In this article, we review research on perceptual-cognitive skills training and describe future research areas focusing on a number of key theories and principles. The main aim of any training intervention should be the efficacy of retention and transfer of learning from training to field situations, which should be the key consideration when designing the representative tasks used in perceptual-cognitive skills training. We review the principles that seek to create practice tasks that replicate those found in the field, so as to increase the amount of transfer that occurs. These principles are perception-action coupling, the contextual interference effect and contextual information, which suggest there should be a high level of similarity between training and real-life performance when designing perceptual-cognitive skills training. In the final section, we discuss the transfer of retained skill acquisition from perceptual-cognitive skills training to field performance, which we suggest to be the key area for future research in this area.